2014
DOI: 10.3174/ajnr.a3870
|View full text |Cite
|
Sign up to set email alerts
|

Diffusion-Weighted Imaging Score of the Brain Stem: A Predictor of Outcome in Acute Basilar Artery Occlusion Treated with the Solitaire FR Device

Abstract: BACKGROUND AND PURPOSE:The prognosis for ischemic stroke due to acute basilar artery occlusion is very poor: Early recanalization remains the main factor that can improve outcomes. The baseline extent of brain stem ischemic damage can also influence outcomes. We evaluated the validity of an easy-to-use DWI score to predict clinical outcome in patients with acute basilar artery occlusion treated by mechanical thrombectomy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
32
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(37 citation statements)
references
References 22 publications
(41 reference statements)
4
32
1
Order By: Relevance
“…The previously identified factors independently associated with a good outcome after endovascular therapy in posterior circulation stroke included a low baseline NIHSS, successful reperfusion, a history of smoking, a high DWI‐Acute Stroke Program Early CT Score (ASPECTS), a shorter time to the start of procedure, a shorter time to reperfusion, better collateral status, and magnetic resonance imaging–based patient selection 3, 7, 9, 18, 19. Recently, Gory et al reported that only the failure to achieve successful reperfusion was an independent predictor of mortality at 3 months, in patients with acute BAO who underwent thrombectomy 20.…”
Section: Discussionmentioning
confidence: 99%
“…The previously identified factors independently associated with a good outcome after endovascular therapy in posterior circulation stroke included a low baseline NIHSS, successful reperfusion, a history of smoking, a high DWI‐Acute Stroke Program Early CT Score (ASPECTS), a shorter time to the start of procedure, a shorter time to reperfusion, better collateral status, and magnetic resonance imaging–based patient selection 3, 7, 9, 18, 19. Recently, Gory et al reported that only the failure to achieve successful reperfusion was an independent predictor of mortality at 3 months, in patients with acute BAO who underwent thrombectomy 20.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, in the study by Karameshev et al, 14 the DWI pc-ASPECTS was not significantly associated with outcome after adjusting for NIHSS, Glasgow Coma Scale, and other DWI scoring systems. Mourand et al 11 also reported that a DWI pc-ASPECTS of ≥7 was not statistically relevant for predicting good outcome in a univariate logistic regression analysis. These discrepancies might be because of differences among studies in patient selection criteria, treatment methods, recanalization results, or the time windows between onset and treatment.…”
Section: Discussionmentioning
confidence: 99%
“…35 Single-centre studies with samples less than 100 patients have shown good functional outcomes following thrombectomy of the basilar artery, ranging from 30% 36,37 to 48%. [38][39][40] Experience at the Karolinska Hospital showed a 57% rate of good functional outcome (95% CI 37% to 75%), and of 73% (95% CI 50% to 89%) when there were no signs of acute infarction prior to treatment, with about 21% mortality. 41 Recanalization rates over 75% were reported with new generation devices 37,42 as well as with older generation devices in the MERCI and multi-MERCI trials but with lower benefit.…”
Section: Aspects To Be Considered In Mechanical Thrombectomymentioning
confidence: 99%
“…60 A smaller study from the same centre on 31 consecutive patients, focusing on basilar artery occlusion treated with Solitaire FR device, found a good correlation between brainstem DWI score <3 and favorable clinical outcome. 40 The prospective, single-arm multicentre DEFUSE-2 trial showed favorable clinical outcomes in patients selected for endovascular treatment with MRI perfusion-weighted imaging (PWI) mismatch in MCA or ICA occlusions (n ¼ 98, about half pre-treated with IVT). 61 Perfusion-CT-based imaging: A multicentre analysis of 165 patients, the vast majority of whom underwent endovascular or intravenous recanalization treatment, showed independent prognostic value of core and penumbra volumes on clinical outcome.…”
Section: 12mentioning
confidence: 99%